Deteksi Dini Penurunan Fungsi Ginjal Melalui Pemeriksaan eGFR dan Kreatinin pada Masyarakat Kelurahan Tanjung Duren Selatan - Soni, Yulfitra; Santoso, Alexander Halim; Destra, Edwin; Wijaya, Bryan Anna; Setiawan, Fiona Valencia (Jurnal Masyarakat Mengabdi Nusantara, 2025)
Kidney dysfunction often remains undetected in its early stages due to minimal clinical symptoms. Serum creatinine and estimated glomerular filtration rate (eGFR) examinations are the main parameters to assess kidney filtration function. Lifestyle factors such as a high-sodium diet play a role in accelerating the decline in kidney function. Creatinine and eGFR examinations were performed by taking venous blood from 104 adult participants. Samples were analyzed in the laboratory, while education was provided directly to all participants after blood sampling, focusing on reducing sodium consumption and improving diet. The examination showed that the average creatinine level was still within normal limits, but the eGFR value of some participants showed a decline in kidney function. The agreement between the two parameters reinforces the importance of laboratory examinations in detecting the risk of declining kidney function. Education successfully conveyed information about the effect of salt consumption on kidney health. eGFR and creatinine examinations are effective steps to detect the risk of kidney dysfunction in asymptomatic populations. Education about reducing sodium and improving diet plays an important role in preventing progressive kidney damage.